Optimizing optical outcomes of intraocular lens implantation by achieving centration on visual axis - Roop; Prakhyat Roop (Indian Journal of Ophthalmology, 2017)
In existing designs of intraocular lenses (IOLs), optical outcomes are compromised even after perfectly executed surgery. The reason for this is misalignment of optical axis of the eye and its visual axis. There is a need to design an IOL which compensates for this misalignment and hence enhances the optical outcomes of cataract surgery. The present innovation attempts to fulfill this unmet need and optimizes optical outcomes of all IOLs of different optical profiles – spherical, aspheric, toric, and multifocal. In addition, the improvised design of IOL offers other benefits such as delaying the formation of after-cataract and ameliorating negative dysphotopsia.